2017
DOI: 10.1186/s13054-017-1901-0
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy versus an endotracheal tube mounted camera for the peri-interventional visualization of percutaneous dilatational tracheostomy - a prospective, randomized trial (VivaPDT)

Abstract: BackgroundPercutaneous dilatational tracheostomy (PDT) in critically ill patients often involves bronchoscopic optical guidance. However, this procedure is not without disadvantages. Therefore, we aimed to study a recently introduced endotracheal tube-mounted camera (VivaSightTM-SL tube [VST]; ETView, Misgav, Israel) for guiding PDT.MethodsThis was a randomized controlled trial involving 46 critically ill patients who received PDT using optical guidance with a VST or with bronchoscopy. The primary outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Thus far, the VST has shown promising results for endotracheal intubation via supraglottic airway devices [ 11 , 17 ], in mannikins [ 18 22 ] and in a cadaver study [ 23 ]. Furthermore, the guidance of percutaneous dilatational tracheostomy by VST has been evaluated and shown to be feasible [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the VST has shown promising results for endotracheal intubation via supraglottic airway devices [ 11 , 17 ], in mannikins [ 18 22 ] and in a cadaver study [ 23 ]. Furthermore, the guidance of percutaneous dilatational tracheostomy by VST has been evaluated and shown to be feasible [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a small, prospective, randomized trial comparing fiberoptic bronchoscopy (FOB) and an endotracheal tube-mounted camera (VivaSight TM-SL tube [VST]; ETView, Misgav, Israel) for optical guidance of percutaneous dilatational tracheostomy (PDT), Grensemann et al [ 1 ] concluded that visualization of PDT with the VST is not non-inferior to the FOB, but ventilation is superior with less hypercarbia when using the VST. We note that in the FOB group, a thick FOB with an outer diameter of 4.9 mm (Olympus BF-P60; Olympus Medical Systems Corp., Tokyo, Japan) was used.…”
mentioning
confidence: 99%
“…We thank Xue et al for their comments [ 1 ] regarding our article on the peri-interventional visualization of percutaneous dilatational tracheostomy (PDT) [ 2 ].…”
mentioning
confidence: 99%